2009
DOI: 10.4067/s0717-75262009000300009
|View full text |Cite
|
Sign up to set email alerts
|

Síndrome De Fitz-Hugh-Curtis Como Hallazgo Durante Cirugía Ginecológica

Abstract: El síndrome de Fitz-Hugh-Curtis es una perihepatitis producida por una peritonitis secundaria al ascenso de bacterias, como resultado de una enfermedad infl amatoria pélvica. En la etapa crónica se pueden observar adherencias entre la pared abdominal y la superfi cie hepática, caracterizadas por la semejanza a "cuerdas de violín". Esta imagen es considerada criterio diagnóstico. Se presenta un caso de hallazgo de síndrome de Fitz-Hugh-Curtis, pesquisado durante la inspección rutinaria de la cavidad abdominopél… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…10 Among the complications, cases of intestinal obstruction or hemoperitoneum due to rupture of adhesions have been described. 11 Although gynecological symptoms are usually absent, it was rare that it did not manifest in some way before the gynecological examination, both before speculoscopy (cervicitis, discharge), or before the bimanual examination (pain on uterine palpation, mobilization of the cervix, adnexal, pelviperitonitis). 12 Within the laboratory tests, they reflected the existence of inflammatory phenomena, there was leukocytosis with neutrophilia as well as elevated CRP, aminotransferases are usually normal or slightly elevated, which helped us differentiate perihepatitis (SFHC) from hepatitis.…”
Section: Discussionmentioning
confidence: 99%
“…10 Among the complications, cases of intestinal obstruction or hemoperitoneum due to rupture of adhesions have been described. 11 Although gynecological symptoms are usually absent, it was rare that it did not manifest in some way before the gynecological examination, both before speculoscopy (cervicitis, discharge), or before the bimanual examination (pain on uterine palpation, mobilization of the cervix, adnexal, pelviperitonitis). 12 Within the laboratory tests, they reflected the existence of inflammatory phenomena, there was leukocytosis with neutrophilia as well as elevated CRP, aminotransferases are usually normal or slightly elevated, which helped us differentiate perihepatitis (SFHC) from hepatitis.…”
Section: Discussionmentioning
confidence: 99%
“…While in the chronic phase, by laparoscopy or laparotomy, adhesions of the liver capsule to the abdominal wall are observed, typically described as "violin string", that is the diagnostic criteria. It occurs in 12-14% of cases of PID (3,7). The common etiologic agent isolated was N. gonorrhoeae, however since 1985, LopezZeno et al (2), showed that C. trachomatis was the most common germ.…”
Section: Discussionmentioning
confidence: 99%
“…La incidencia es incierta, en el estudio más grande con 3.564 laparoscopías, se diagnosticó este síndrome en 14,8% de las pacientes con infertilidad tubaria; 6,7% en embarazos ectópicos y en 1,4% por otras indicaciones ginecológicas (Hong et al, 2010). Sin embargo, aun existen pocas publicaciones con un reducido número de caso sobre esta patología (Ricci et al, 2009).…”
Section: Introductionunclassified